2019
DOI: 10.1186/s12879-019-4350-3
|View full text |Cite
|
Sign up to set email alerts
|

Type A fulminant Clostridium perfringens sepsis indicated RBC/Hb discrepancy; a case report

Abstract: Background Clostridium perfringens can cause various infections, including food poisoning, gas gangrene, cellulitis and fasciitis. C. perfringens septicemia is rare, but is a known cause of hemolysis by damaging red blood cell, and often proves rapidly fatal in emergency department (ED) situations. Case presentation A previously healthy 76-year-old man presented to the ED 8 h after onset of acute abdominal pain and diarrhea. Lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…At present, it is well known that influenza hemagglutinin readily binds to sialic acid receptors on the membranes of red blood cells, causing red blood cells to clump together or agglutinate . Some bacterial infections cause intravascular hemolysis leading to sepsis, which reduces the red blood cell count and may be why bacterial infections cause more significant reduction in red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is well known that influenza hemagglutinin readily binds to sialic acid receptors on the membranes of red blood cells, causing red blood cells to clump together or agglutinate . Some bacterial infections cause intravascular hemolysis leading to sepsis, which reduces the red blood cell count and may be why bacterial infections cause more significant reduction in red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the detection of C. difficile in the direct environment of the patient, studies have also confirmed the presence of other pathogenic species, such as C. perfringens , C. sporogenes , C. innocuum and C. baratii . These are species which are also detected in other medical facilities and which may constitute a significant disease-causing problem related to HAI [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Analysis of the behaviour of hospital personnel was not a direct goal of this study, but it supplements the conducted research analyses.…”
Section: Discussionmentioning
confidence: 99%
“…次に,この感染症を引き起こす病態であるが,本症例では,胆道系感染が関連していたが,胆道系疾患に対するERCP施行後に感染した症例も見られ,胆道系の炎症が要因の一つとして注目される 12)。ただし,なかには基礎疾患を有さず胃腸炎の症状だけで,目立った手がかりを見出せなかった報告もある 7), 16), 17)。転帰に関しては13例中,11例が死亡しており,やはり救命が難しい病態であることを示している。さらに,死亡例のうち7例が24時間以内に死亡しており,進展が極めて急速であることを物語っている。…”
Section: 考  察unclassified